The Role of Parents in Shaping the Religious Character of Elementary School Children in the Digital Era - Agus M. Sihabudin (Jurnal Penelitian Medan Agama, 2025)
This study aims to describe the role of parents in shaping the religious character of elementary school-aged children in Dusun Ngayung, Sumberagung Village, Plumpang Sub-district, Tuban Regency, particularly in the context of challenges brought by the digital era. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation. The findings indicate that while religious education institutions such as TPQ (Qur'anic learning centers) exist and function in the community, parental involvement plays a more crucial role in embedding religious values. However, many parents have not yet consistently guided their children in religious practice, often due to limited time, low digital literacy, and a tendency to rely solely on formal or non-formal education. The study also found that excessive and unsupervised use of digital media by children tends to weaken their interest and engagement in religious activities. Some parents have made positive efforts by limiting screen time, encouraging daily prayers, and being role models at home, but these practices remain limited in scope. The study concludes that collaborative efforts between parents, educational institutions, and the wider community are essential to foster religious character in children, especially in balancing technological advancement with spiritual development.